Formulation and Evaluation of Transdermal Patches for Antianxiety Drug - Boggula, Narender (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present study was to design, develop, and evaluate a matrix-type transdermal formulation containing buspirone hydrochloride (HCL) for treatment of anxiety with a goal to increase the bioavailability and improve the patient compliance. Materials and Methods: In the present research work, the different concentrations of hydroxypropyl methylcellulose (HPMC) E50, HPMC E15, and Eudragit RS100 were used in combination to optimize the concentration of HPMC E15 and Eudragit RS100 in the formulation of transdermal patches. These different ratios of hydrophilic and hydrophobic polymeric combinations plasticized with dibutyl phthalate by the solvent evaporation technique. The prepared patches were evaluated for their physicochemical characteristics such as thickness, weight and drug content uniformity, moisture content, moisture uptake and folding endurance, and in vitro drug release studies. Optimized formulation was further evaluated by in vivo release study, drug-excipient compatibility, and stability study. Results and Discussion: Effect of permeation enhancers such as oleic acid was studied. The interference of the polymers was ruled out by Fourier transform infrared and ultraviolet-spectroscopic methods. In vitro release studies of buspirone HCL-loaded patches in phosphate buffer (pH, 7.4) were performed using a modified diffusion cell and showed first-order release rate. Skin studies for the transdermal patches were assessed and were found to be free of irritation. In vivo drug release studies had shown release up to 24 h with the release of 73.82% and it was correlated with in vitro studies. The patches were subjected to short-term stability studies and were found stable. Conclusion: It is concluded from the present studies that the transdermal patches of buspirone HCL were capable of exhibiting controlled release with the stability. Studies had shown promising results, and there was a scope for further pharmacodynamic and pharmacokinetic evaluation.